2019
DOI: 10.1177/2047487319843667
|View full text |Cite
|
Sign up to set email alerts
|

Dietary components and risk of cardiovascular disease and all-cause mortality: a review of evidence from meta-analyses

Abstract: Aims The optimal diet for cardiovascular health is controversial. The aim of this review is to summarize the highest level of evidence and rank the risk associated with each individual component of diet within its food group. Methods and results A systematic search of PudMed was performed to identify the highest level of evidence available from systematic reviews or meta-analyses that evaluated different dietary components and their associated risk of all-cause mortality and cardiovascular disease. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 47 publications
0
51
0
5
Order By: Relevance
“…Summary messages regarding dietary protein are presented in table 1. Detailed study7–13 analysis examining protein intake and CVD are presented in online supplementary table 1.…”
Section: Macronutrientsmentioning
confidence: 99%
See 3 more Smart Citations
“…Summary messages regarding dietary protein are presented in table 1. Detailed study7–13 analysis examining protein intake and CVD are presented in online supplementary table 1.…”
Section: Macronutrientsmentioning
confidence: 99%
“…Indeed, randomised controlled trials show that the quality of meat (in addition to the whole diet) is likely to be an important factor to consider in explaining this relationship, with evidence suggesting that the addition of lean red meat to an already low saturated fat cardioprotective diet does not impact negatively on blood lipids 9. The saturated fat content of the comparison diet10 may be an additional piece of the puzzle in explaining the impact dietary protein (and its source) has on cardiovascular health 11…”
Section: Macronutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, TMAO can also be directly absorbed from dietary sources, mainly fish [86]. Fish has been long linked with positive health effects including protection from cardiovascular diseases [87]. For example a recent report on the European Prospective Investigation Into Cancer and Nutrition (EPIC)-Oxford study concluded that fish eaters and vegetarians had 13% lower rates of ischemic heart disease than meat eaters [88] and dietary patterns rich in fish, such as the Nordic diet and Mediterranean diet, are among most stably reported health-beneficial dietary schemes [3].…”
Section: Effects Of a Healthy Nordic Diet On The Gut Microbiota And Dmentioning
confidence: 99%